2012
DOI: 10.3899/jrheum.111608
|View full text |Cite
|
Sign up to set email alerts
|

Persistent or New Onset Microscopic Hematuria in Patients with Small Vessel Vasculitis in Remission: Findings on Renal Biopsy

Abstract: Microscopic hematuria in patients with renal vasculitis otherwise in remission could represent chronic glomerular injury from prior episode of vasculitis or may represent new glomerular pathology. Renal biopsy should be considered in these patients to guide therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 15 publications
5
39
0
Order By: Relevance
“…In this retrospective study of 96 patients with pauci-imune glomerulonephritis it was questioned whether microscopic haematuria in patients with renal vasculitis in clinical remission could represent chronic glomerular injury from prior episodes of disease-activity or may represent new glomerular pathology [1]. We found that in general, haematuria disappears between three and six months after diagnosis and start of induction therapy and that the disappearance coincides in time with stabilisation of renal function.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…In this retrospective study of 96 patients with pauci-imune glomerulonephritis it was questioned whether microscopic haematuria in patients with renal vasculitis in clinical remission could represent chronic glomerular injury from prior episodes of disease-activity or may represent new glomerular pathology [1]. We found that in general, haematuria disappears between three and six months after diagnosis and start of induction therapy and that the disappearance coincides in time with stabilisation of renal function.…”
Section: Discussionmentioning
confidence: 80%
“…The small-vessel vasculitides consist of a heterogeneous group of uncommon systemic multi-organ disorders that are prone to cycles of remission and relapse [1]. These vasculitides include Granulomatosis with Polyangiitis (GPA), Microscopic Polyangiitis (MPA), and eosinophilic Granulomatosis with Poly-Angiitis (eGPA) [1].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations